Photocatalytic water splitting by utilising oxide semiconductor materials - Lai, H; Hung-Chun Lai (2012)
This thesis reports the study of metal oxide semiconductors for the application of photoelectrochemical water splitting with a particular emphasis on both anion and cation-doped zinc oxides. A study of the mechanisms of visible light absorption in both anion and cation-doped ZnO semiconductors, the potentials of metal oxide materials modified by impurities as one of the ideal photocatalysts in harvesting solar light has been explored. X-ray photoelectron spectroscopy (XPS) and UV-Vis spectroscopes have been performed to establish the electronic structures of anion and cation-doped ZnO. Aluminium impurities in ZnO thin films reveal the relationship between the bandgap broadening and the so-called Burstein Moss effect. Both cadmium and sulphur dopants were incorporated in ZnO either as powders by the solid state synthesis or as thin films by spray pyrolysis technique. Cadmium and sulphur dopants demonstrate effective electronic bandgap reduction and an increasing absorption of visible light. Furthermore, the incorporation of cadmium and sulphur in ZnO were prepared as photoanodes and evaluated in a custom-built photoelectrochemical workstation for the measurement of photon energy conversion efficiencies.